PENGARUH VARIASI GAS PELINDUNG PADA TIG BRAZING ANTARA CEMENTED CARBIDE DAN BAJA KARBON TERHADAP KEKUATAN GESER DAN STRUKTUR MIKRO - Muhammad Choirul Faizin; Yoyok Winardi; Nanang Suffiadi Ahmad (Universitas Muhammadiyah Ponorogo, 2022)
Dissimilar metals have found wide use in electric power generation, electronics, reactors, nuclear, petrochemical, chemical industries, civil construction, vessels, and heat exchange as well as several other industries. TIG welding (Tungsten Inert Gas Welding) is a type of electric welding that uses tungsten as the electrode material that is not consumed. Brazing is a way of joining metal materials through a heating process with an adhesive or filler material that has a melting point below the material to be combined or connected. The main objective of this study was to determine the shear strength and microstructure of the weld area that was joined by the brazing method. From the results of the shear strength test, there is a comparison of the difference in the shear stress strength. The results obtained indicate that where the shear stress test at a flow rate of 5 liters/minute of protective gas gets the highest shear stress value of 108 N/mm2, compared to the shear stress test with a gas flow rate of 10 liters/minute, the shear stress value is equal to 97 N/mm2, but at the protective gas flow rate of 15 liters/minute the lowest shear stress value was 76 N/mm2. The results of the microstructure obtained the result that the protective gas flow rate of 15 liters/minute got the lowest value due to a decrease in the amount of Si elements, resulting in the lowest shear stress value.